Weighted kneading theory of one-dimensional maps with a hole - J. Leonel Rocha; J. Sousa Ramos (International Journal of Mathematics and Mathematical Sciences)
The purpose of this paper is to present a weighted kneading theory for one-dimensional maps with a hole. We consider extensions of the kneading theory of Milnor and Thurston to expanding discontinuous maps with a hole and introduce weights in the formal power series. This method allows us to derive techniques to compute explicitly the topological entropy, the Hausdorff dimension, and the escape rate.